Space-time conceptualizations among Malaysian Chinese bilinguals / David Mahlum - David , Mahlum (2019)
A questionnaire and experiment were conducted to investigate whether there is evidence for linguistic relativity among the Malaysian Chinese population. In order to make the influence of language on thought measurable, this study used the principles of conceptual metaphor theory and the conceptual domains of SPACE and TIME. The research aimed to detect the degree to which participants’ conceptualizations of time were conditioned by space-to-time metaphors (STMs) in their primary language (English and Mandarin). A psycholinguistic experiment conducted designed after Fuhrman et. al. 2011 to accomplish this aim. Analysis of the results reveal no influence of STMs on conceptualization of time. Rather, the data revealed bias in a direction opposite of what was predicted. It is concluded that the findings of the current study run counter to the claims of linguistic relativity. More accurate knowledge of the usage of STMs in English and Mandarin is needed as well as more empirical research isolating the influence of STMs on conceptualizations of time.